Iron, Cobalt, and Gadolinium Transport in Methanogenic Granules Measured by 3D Magnetic Resonance Imaging - Bartacek, Jan; Vergeldt, Frank J.; Maca, Josef; Gerkema, Edo; Van As, Henk; Lens, Piet N. L. (Frontiers in Environmental Science, 2016)
Description of processes such as bioaccumulation, bioavailability and biosorption of heavy metals in biofilm matrixes requires the quantification of their transport. This study shows 3D MRI measurements of the penetration of free (Fe2+, Co2+ and Gd3+) and complexed ([FeEDTA]2- and [GdDTPA]2-) metal ions in a single methanogenic granule. Interactions (sorption or precipitation) between free metals and the biofilm matrix result in extreme shortening of the spin-spin relaxation time (T2) and a decrease of the amplitude (A0) of the MRI signal, which hampers the quantification of the metal concentration inside the granular sludge matrix. MRI images clearly showed the presence of distinct regions (dead or living biomass, cracks and precipitates) in the granular matrix, which influenced the metal transport. For the free metal ions, a reactive barrier was formed that moved through the granule, especially in the case of Gd3+. Chelated metals penetrated faster and without reaction front. Diffusion of [GdDTPA]2- could be quantified, revealing the course of its transport and the uneven (0.2 – 0.4 mmol·L-1) distribution of the final [GdDTPA]2- concentration within the granular biofilm matrix at equilibrium.